PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DENGAN MEDIA FLASHCARD UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS II SDN 064971 MEDAN TEMBUNG - Linda E M Simatupang; Indah Pratiwi; Roida Siboro (STKIP Subang, 2024)
This research was conducted based on the problem of critical thinking skills that are still low in students. The purpose of this study was to determine the improvement of students' critical thinking skills using a problem-based learning model with flash card media in learning Pancasila education in class 2 SDN 074971 Medan Tembung. The research method used was Classroom Action Research (PTK), which was conducted through two cycles. The research process consists of four stages, namely planning, implementation, observation/data collection, and reflection. The subjects of this research consisted of 22 students of grade 2 SDN 074971 Medan Tembung. Data collection used instruments in the form of observation sheets and tests. The results showed that the application of problem-based learning model with flash card media succeeded in improving students' critical thinking skills. This can be seen from the increase in the average score in each cycle. In the pre-cycle stage, the average critical thinking score was 18% and increased in cycle I to 50%, then increased again in cycle II to 86%.